Comparison of energy efficiency and costs related to conventional and LED road lighting installations. (1st September 2022) - Davidovic, M.; Kostic, M.
Abstract: Comparison of conventional (usually high-pressure sodium (HPS)) and LED luminaires in street/road lighting is not often based on photometrically equivalent lighting solutions and/or correct economic analysis, which may lead to either overestimation or underestimation of savings of any kind. Therefore, this paper presents a correct methodology for the determination of actual energy efficiency and cost indicators in street/road lighting. Both neutral white (NW) and warm white (WW) LEDs, all relevant street/road lighting classes and pole layouts were considered. Analyzing optimal lighting solutions, characterized by the lowest installed power, it was shown that when considering mesopic effects the average energy savings achieved comparing LED (NW and WW) with HPS lighting solutions amounted to 41–62% and 29–59%, respectively, while the ratio between the total costs of the comparable LED (NW and WW) and HPS lighting solutions belonged to the ranges 0.59–1.26 and 0.61–1.14, respectively. An expanded sensitivity analysis of the costs, carried out considering not only the usually taken discount and electricity cost rates, but also the LED package lifetime, showed that the last only slightly influences the total costs. The effects of the use of more efficient LED packages expected in the near future were also analyzed. Highlights: Comparison of equivalent HPS, MH and LED street/road lighting solutions. Methodology for determining actual energy efficiency and cost indicators. NW/WW LEDs with luminous efficacy up to 160 lm/W and the forthcoming with 190 lm/W. Study of all street lighting classes/pole layouts under photopic/mesopic conditions. LEDs are recommended for street/road lighting instead of conventional luminaires.